Precopulatory but not postcopulatory male reproductive traits diverge in response to mating system manipulation in Drosophila melanogaster. Issue 23 (30th October 2017) - Wensing, Kristina U.; Koppik, Mareike; Fricke, Claudia
Abstract: Competition between males creates potential for pre‐ and postcopulatory sexual selection and conflict. Theory predicts that males facing risk of sperm competition should evolve traits to secure their reproductive success. If those traits are costly to females, the evolution of such traits may also increase conflict between the sexes. Conversely, under the absence of sperm competition, one expectation is for selection on male competitive traits to relax thereby also relaxing sexual conflict. Experimental evolution studies are a powerful tool to test this expectation. Studies in multiple insect species have yielded mixed and partially conflicting results. In this study, we evaluated male competitive traits and male effects on female costs of mating in Drosophila melanogaster after replicate lines evolved for more than 50 generations either under enforced monogamy or sustained polygamy, thus manipulating the extent of intrasexual competition between males. We found that in a setting where males competed directly with a rival male for access to a female and fertilization of her ova polygamous males had superior reproductive success compared to monogamous males. When comparing reproductive success solely in double mating standard sperm competition assays, however, we found no difference in male sperm defense competitiveness between the different selection regimes. Instead, we found monogamous males to be inferior in precopulatory competition, which indicates that in our system, enforced monogamy relaxed selection on traits important in precopulatory rather than postcopulatory competition. We discuss our findings in the context of findings from previous experimental evolution studies in Drosophila ssp . and other invertebrate species. Abstract : We used experimental evolution to study the evolution of a suite of pre‐ and postcopulatory male reproductive traits in response to manipulating sexual selection and sexual conflict in Drosophila melanogaster through enforcing monogamy or sustaining polygamy. We found that enforcing monogamy led to relaxed selection on pre‐ but not postcopulatory traits in our system. Collectively, our data together with results from other studies indicate that we need to take into account a broad spectrum of traits to fully capture the evolutionary responses in male reproductive success to altered sexual selection pressures.